Addressing metaphors and symbols in an ESL reading comprehension class / Mak Kem Seng - Mak, Kem Seng (UiTM Kedah, 2003)
Our lives are affected, knowingly or unknowingly through the usage and influence of metaphors and symbols. This paper attempts to highlight an overview of their presence as seen from the aspect of ESL reading comprehension by a group of selected respondents. It also provides some insights into the roles of metaphors and symbols being utilised in the ESL learning class. The impact and application of the roles played by metaphors and symbols have been greatly used by writers. This paper also seeks to focus on analytical and descriptive details such as looking at the students' perception of metaphors and symbols as used in certain reading comprehension passages, the percentage of students who were able to interpret the precise meaning of metaphors and symbols correctly, and lastly the interface of students' background knowledge with the presupposed meaning of metaphors and symbols. Using open-ended questions, the responses of respondents regarding the usage and influence of metaphors and symbols in an ESL reading comprehension class were analysed. It is hoped that the findings will be beneficial to educators and readers alike and will serve as a framework for future research into the elements of metaphors and symbols as used in the literary field.